Σχεδιαστική βελτίωση υβριδικού ρομποτικού συστήματος Gantry και σχεδιασμός υποσυστήματος Δέλτα - Κατσίφλης, Νεόφυτος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The current thesis project is a continuance of a previous dissertation which is developed with the design optimization of a robot hybrid system (type Gantry) and the design of a Delta Robot. The combination of two robot system assist on the implementation of automate movements in three directions x,y,z. The first chapter is concerned on the aim of the dissertation, a general review on the robot field. Particular attention was drawn to industrial robots with specialization of Gantry and Delta. Moving forward to the second chapter the systems specifications and various construction limitations are also examined since there is an analysis on how the robot systems were implemented on the early stages and the developments were done throughout the years. On the third chapter there is an investigation of the statically and dynamical construction elements of the robot systems Gantry with a combination of theoretical and computational methods using Solidworks software. On chapter four a theoretical analysis on the bearings of the whole construction is analyzed which is the type of bearings are selected. In chapter five is examined both design and kinematic analysis of the robot Delta. The kinematic simulation is implemented with the use of Matlab software for the results of the final dimensions of the robot which meet the required specifications. Furthermore, it is examined the statistic and final constructive elements which are included on the robots with the use of calculation method. Basic factors for setting the whole construction were the findings of the statistical analysis and the distribution of the elements to the Cyprus markets and the university. Finally, the findings of the study demonstrate that the design stages of the robotic system served with the followed methodology supports the system to be operational and feasible for construction.
Keywords: Robot hybrid system; Delta Robot; Industrial robots; Gantry; Delta; Ρομποτικό υβριδικό σύστημα; Δέλτα ρομπότ; Βιομηχανικά ρομπότ; Δέλτα